Employability and Job Performance as Links in the Relationship Between Mentoring Receipt and Career Success: A Study in SMEs. (April 2016) - Bozionelos, Nikos; Kostopoulos, Konstantinos; Van der Heijden, Beatrice; Rousseau, Denise M.; Bozionelos, Giorgos; Hoyland, Thomas; Miao, Rentao; Marzec, Izabela; Jędrzejowicz, Piotr; Epitropaki, Olga; Mikkelsen, Aslaug; Scholarios, Dora; et al.
This study developed and tested a model that posited employability and job performance as intervening variables in the relationship between receipt of mentoring and career success. Participants were 207 information technology (IT) professionals employed in small and medium-sized enterprises (SMEs) in three European countries. Mentoring receipt was related to both employability and job performance. Employability mediated the relationship of mentoring receipt with objective and subjective career success, as well as its relationship with job performance. The findings indicate that receipt of mentoring is connected to job performance, a link that has hitherto lacked empirical evidence. In addition, they suggest a pivotal role for employability in the relationship of mentoring receipt with job performance and career success. Overall, this study helps unveil the mechanism through which mentoring affects career outcomes. Moreover, it shows that the benefits of mentoring hold outside the context of large corporations.